UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA DARING ZOOM MEETING - Meriyanti Meriyanti (GURUKU, 2022)
The purpose of this research is to improve student learning outcomes through used online media “zoom meeting” in PAI learning. Classroom Action Research (CAR) was conducted in 2 cycles. The research subjects were students of X IPS 2 (second social 10th grade) SMA Negeri 1 Kandis which consisted of 30 students. The Data collection technique used in this research was student learning outcomes. The results of this research indicate that the application of online media ‘zoom meeting’ can improve student learning outcomes. It can be seen from the percentage of indicator students participating in online learning using the zoom meeting media has increased. The percentage of student results in the first cycle the average percentage is 27%. In cycle II the average percentage of student learning outcomes increased to 73% and has reached an achievement indicator of 70%. Based on the results of the analysis of research data, it can be concluded that there is a significant increase of students learning outcomes through online media zoom meeting in PAI learning in X IPS 2 SMA Negeri 1 Kandis in academic year 2021/2022